Buddhism and the Sinhala Writing Tradition. - Jayaweera, Ruwan (Advances in Social Sciences Research Journal, 2019)
Abstract The aim of this Paper is to study the influence of Buddhism on Sinhala language. Sinhala language has a continual history, which dates back to thousands of years. It seems to be a language with written evidences of great history, which dates at least to the 3rd century B.C. Though several evidences could be presented to confirm that there was a writing practice using Sinhala language (Heḷa Basa) after the arrival of Prince Vijayain Sri Lanka that tradition developed systematically after the introduction of Buddhism as by Venerable Mahinda in 3rd century B.C. He acquainted a Brāhmī alphabet becomingly the Brāhmī scripts in Asoka inscriptions to expand the writing methodology in the island. In addition to that he translated Pali commentaries into Sinhala and that literary activity caused to spring a sophisticated Buddhist literature after -wards. The Brāhmīalphabet expanded in its evolution of Pali and Sanskrit scripts under the influence of Buddhism in the course of the time. Though Sinhala wordstock is an interesting combination of borrowed words from various languages, it should be mentioned that a considerable amount of Paliand Sanskrit words could be identified in the Sinhala tongue which have entered as homogeneous or derived words under the influence of Theravāda or Mahāyāna Buddhism. A special attention has been given to explore the Sinhala wordstock which has expanded with such kind of words, as a morphological study. There is a developed literary tradition in Sinhala language which possesses written evidence since the third century B.C. Sinhala language together with a Buddhist literary tradition evolved gradually and signs of Diglossia began to emerge in the course of time. While the spoken practice rapidly evolved by contacting with other languages as well as it developed as a living language, however writing on the other hand had barriers. As a result the difference between the writing and speech (colloquial practice) expanded. The Buddhist influence is visible explicitly not only in written Sinhala but also in colloquial Sinhala. The attempt of this article to study this language form nourished by Buddhism comprehensively. Keywords :- Derivation, Borrowing Homogeneous words., Derived words, Folk Religion, Colloquial Sinhala. The aim of this Paper is to study the influence of Buddhism on Sinhala language. Sinhala language has a continual history, which dates back to thousands of years. It seems to be a language with written evidences of great history, which dates at least to the 3rd century B.C. Though several evidences could be presented to confirm that there was a writing practice using Sinhala language (Heḷa Basa) after the arrival of Prince Vijayain Sri Lanka that tradition developed systematically after the introduction of Buddhism as by Venerable Mahinda in 3rd century B.C. He acquainted a Brāhmī alphabet becomingly the Brāhmī scripts in Asoka inscriptions to expand the writing methodology in the island. In addition to that he translated Pali commentaries into Sinhala and that literary activity caused to spring a sophisticated Buddhist literature after -wards. The Brāhmīalphabet expanded in its evolution of Pali and Sanskrit scripts under the influence of Buddhism in the course of the time. Though Sinhala wordstock is an interesting combination of borrowed words from various languages, it should be mentioned that a considerable amount of Paliand Sanskrit words could be identified in the Sinhala tongue which have entered as homogeneous or derived words under the influence of Theravāda or Mahāyāna Buddhism. A special attention has been given to explore the Sinhala wordstock which has expanded with such kind of words, as a morphological study. There is a developed literary tradition in Sinhala language which possesses written evidence since the third century B.C. Sinhala language together with a Buddhist literary tradition evolved gradually and signs of Diglossia began to emerge in the course of time. While the spoken practice rapidly evolved by contacting with other languages as well as it developed as a living language, however writing on the other hand had barriers. As a result the difference between the writing and speech (colloquial practice) expanded. The Buddhist influence is visible explicitly not only in written Sinhala but also in colloquial Sinhala. The attempt of this article to study this language form nourished by Buddhism comprehensively. Keywords :- Derivation, Borrowing Homogeneous words., Derived words, Folk Religion, Colloquial Sinhala.